2007
DOI: 10.1002/gps.1789
|View full text |Cite
|
Sign up to set email alerts
|

Depression and chronic medical illnesses in Asian older adults: the role of subjective health and functional status

Abstract: Most comorbid associations of depressive symptoms with specific chronic illnesses are explained by accompanying poor self-reported health and functional status, but some illnesses probably have a direct psychobiological basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
91
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 32 publications
12
91
1
1
Order By: Relevance
“…11,39 Age and chronic medical conditions were also significantly predictive of depressive symptoms in both bivariate and multivariate analyses, consistent with prior studies. 40,41 Some studies have indicated that the prevalence of depression declines from midlife to older adulthood. 27 This was partially supported in the current study, as the quadratic age trend indicated that the odds of moderate depressive symptoms declined somewhat from age 60 to 72 and only increased thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…11,39 Age and chronic medical conditions were also significantly predictive of depressive symptoms in both bivariate and multivariate analyses, consistent with prior studies. 40,41 Some studies have indicated that the prevalence of depression declines from midlife to older adulthood. 27 This was partially supported in the current study, as the quadratic age trend indicated that the odds of moderate depressive symptoms declined somewhat from age 60 to 72 and only increased thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the National University of Singapore Institutional Review Board, and all participants gave signed informed consent. The details of the Singapore Longitudinal Ageing Study have been described in previous publications (23,24).…”
Section: Study Populationmentioning
confidence: 99%
“…Stress affects the immunity and causes chronic medical diseases including coronary artery disease . This study did not report the prevalence of chronic medical diseases which is associated with higher level of stress, poor subjective health and impaired functional status (Niti et al, 2007).…”
Section: Discussionmentioning
confidence: 81%